INTEGRATION OF THE MATHEMATICS TEXTBOOKS IN THE TEACHING/LEARNING PROCESS - IULIANA MARCHIŞ (Studia Universitatis Babes-Bolyai, 2010)
ABSTRACT. Research shows, that textbooks are important in teaching and learning Mathematics. The goal of the article is to study how teachers and their pupils use the mathematics textbook. The research tool is a questionnaire; the sample is made of 60 mathematics teachers. The results show that teachers mostly use the textbook to prepare their lessons and to assign homework for their pupils. Students mostly use the textbook to solve the given problems. There is a correlation between the teacher guidance on textbook use and how pupils use their textbooks.